Formal and Artistic Structure in the Jordanian Short Poem: An Analytical Study of Mukhtar's Models - Al-Kharsh, Ahmad Ghaleb; Al-Kayed, Ahmed Faisal (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to explore the formal and artistic structure of the Jordanian short poem, with a focus on the elements that define its essence Methods: Employing a stylistic approach, the researcher analyzed the formal and artistic structure of Jordanian short poems by examining selected poetic texts that reflect these characteristics. These poems were chosen for their stylistic significance in both form and technique. Results: The formal and artistic structure of the Jordanian short poem exhibited a range of variations. From a formal perspective, these poems displayed closed circular, open circular, and spiral structures. Artistically, Jordanian poets employed a variety of techniques, including the prominent use of keywords, condensation, narrative storytelling, and effective introductions and conclusions. Conclusions: Despite the specific features inherent in short poems, Jordanian poets demonstrated their ability to represent diverse poetic forms while employing artistic techniques that conveyed their individual visions and emotional perspectives.